Komunikasi Pemasaran Kamar Hotel Melalui Media Sosial Tiktok Dalam Meningkatkan Minat Hunian - Deco Viesta Alam; M. Miftah Farid (Journal of Innovative and Creativity, 2026)
The development of social media has brought significant changes to the marketing communication strategies of the hospitality industry, particularly in efforts to increase room occupancy rates. TikTok has become one of the most widely used platforms due to its ability to present visual content creatively, concisely, and easily reach a broad audience. This research aims to analyze hotel room marketing communication thru the social media platform TikTok in order to increase occupancy interest. The research method used is qualitative with a descriptive approach. Data collection techniques were carried out thru observation of hotel room promotion content on TikTok, documentation, and relevant literature studies. The research results indicate that utilizing TikTok as a marketing communication medium is effective in attracting the attention of potential guests thru informative, visually appealing, and persuasive content, such as showcasing room facilities, price promotions, and guest experiences. Additionally, audience interaction thru comment, like, and share features contributes to building trust and increasing consumer engagement. Thus, TikTok serves as a strategic and effective marketing communication medium in increasing interest in hotel room occupancy.